Tutorial Session and Sunday Classes an Ideal Approach to Enhance Academic Performance - Garcia, Gary C. (JPAIR Institutional Research, 2013)
To leave no child behind, educators must initiate a program that would address students' problem on the Academic and educational promotion. Intervention such as tracking students' weakness and identifying factors that affect most of their focus towards educational standards is definitely part of the plan. In most cases, tutorial turn out to be the conduit variables to learning. However, the behavior of an individual was considered a key to success in education. Thus, religious students were assumed to behave more and will perform better during classes, religious activity engagement appears to offer a positive influence in learning process. The study was intended to determine the effects of Saturday Tutorial Session and Sunday Religious Classes in the academic performance of the Child Development Program (CDP) beneficiaries. Descriptive-survey method of research using purposive sampling was utilized. Only the high school CDP beneficiaries and their teachers were chosen as the respondents. Results reveal that sickness, as the cause of the students' low performance in academic is still dominant in basic education. It also reveal that the diversity in teaching is not 100 percent acquired up to this very moment considering that the traditional teaching strategies of teacher was considered as one of the causes of the students low performance in academic. Generally, results implied that the combined tutorial class and religious attendance are very good recipe to enhance academic performance of students.
Keywords: tutorial session; Sunday classes; academic performance